Examining the Relationship between Job Characteristics and Job Satisfaction among Southern Prison Staff. Issue 2 (14th March 2020) - Keena, Linda D.; Lambert, Eric G.; Haynes, Stacy H.; May, David; Buckner, Zachary
ABSTRACT: The job characteristics model was used to explain job satisfaction at a large southern prison. The effects of job variety, role clarity, views of supervision, views of training, perceived dangerousness of the job, and job autonomy on job satisfaction were studied. Using data from 322 staff members, the study found positive job characteristics (i.e., job variety, supervision, training, and lower perceived dangerousness of job) were associated with greater job satisfaction. Job autonomy was non-significant. Job variety, quality of supervision, and training views were positively associated with job satisfaction for all staff and security officers, whereas dangerousness of job was negatively associated. Role clarity mattered for all staff, but not security officers. Reasons for both significant and non-significant relationships were discussed.